Heat stress‐induced oviposition behavioral change correlates with sperm damage in the pine sawyer beetle, Monochamus alternatus - Li, Hui; Li, Shouyin; Chen, Jin; Tan, Yushan; Ye, Jianren; Hao, Dejun (Pest management science, 2024)
Background Global climate change is causing an increase in extreme high temperatures (EHTs), which subject insects to unprecedented stress. Behavior plasticity in response to EHTs, particularly oviposition behavior, is important for the persistence and outbreak of insect populations. Investigating the plasticity of oviposition behavior and its underlying mechanisms has theoretical importance to pest management, but knowledge gaps still remain. Results Herein, we characterized the reproductive traits of Monochamus alternatus, a dominant insect vector of the destructive pine wilt disease, including oviposition behavioral patterns, fecundity, offspring fitness and sperm viability, under simulated heatwave conditions in the laboratory. The results showed that (i) EHTs induced a novel oviposition behavior, whereby females deposited multiple eggs into a single groove rather than laying one egg per groove under normal condition; (ii) EHTs exerted stage‐ and sex‐specific effects on fecundity, offspring fitness and sperm viability; and (iii) there was a significant correlation between frequency of the novel oviposition strategy and sperm viability. Conclusion We hypothesized that this beetle pest has the ability to flexibly shift towards a low‐cost oviposition strategy to counteract the fitness costs caused by heat stress. Taken together, these findings provide a theoretical foundation for personalized pest management strategies in the context of climate change. © 2024 Society of Chemical Industry. Extreme high temperatures have triggered a novel oviposition model in the pine sawyer beetle by affecting sperm vitality, which may help the species mitigate the negative effects of high temperatures by conserving more energy.